A Novel Iterative-Learner Simulation Model: Fellows as Teachers - Tofil, Nancy M. (The Accreditation Council for Graduate Medical Education, 2014)
BACKGROUND: Simulation is an effective method for teaching clinical skills but has not been widely adopted to educate trainees about how to teach. OBJECTIVE: We evaluated a curriculum for pediatrics fellows by using high-fidelity simulation (mannequin with vital signs) to improve pedagogical skills. INTERVENTION: The intervention included a lecture on adult learning and active-learning techniques, development of a case from the fellows' subspecialties, and teaching the case to residents and medical students. Teaching was observed by an educator using a standardized checklist. Learners evaluated fellows' teaching by using a structured evaluation tool; learner evaluations and the observer checklist formed the basis for written feedback. Changes in fellows' pedagogic knowledge, attitudes, and self-reported skills were analyzed by using Friedman and Wilcoxon rank-sum test at baseline, immediate postintervention, and 6-month follow-up. RESULTS: Forty fellows participated. Fellows' self-ratings significantly improved from baseline to 6-month follow-up for development of learning objectives, effectively reinforcing performance, using teaching techniques to promote critical thinking, providing constructive feedback, and using case studies to teach general rules. Fellows significantly increased agreement with the statement “providing background and context is important” (4.12 to 4.44, P  =  .02). CONCLUSIONS: Simulation was an effective means of educating fellows about teaching, with fellows' attitudes and self-rated confidence improving after participation but returning to baseline at the 6-month assessment. The simulation identified common weaknesses of fellows as teachers, including failure to provide objectives to learners, failure to provide a summary of key learning points, and lack of inclusion of all learners.